Interaksi Simbolik Tradisi Pandhaba di Situbondo - Jamiatul Hasanah; Wisri Wisri (Maddah : Jurnal Komunikasi dan Konseling Islam, 2021)
Abstract According to the definition of society from generation to generation, the rokat pandhaba tradition is a ritual to save a pandhaba child from bad luck and evil. as well as a medium to protect from all forms of distress which is symbolized by the disturbance of the bhatarakala by the community, and is said to be disturbing the life journey of a pandhaba child. Rokat pandhaba is a tradition that has been preserved for generations by the people of Jatisari Arjasa village, Arjasa district, Situbondo district. This article will discuss how the symbolic interaction of the pandhaba tradition. The method used is a qualitative method because the research subject that is the focus is on the symbolic interaction of the pandhaba tradition. The results show that from this ruwat or rokat pandhaba culture, there is a philosophy that the problem of destiny must be believed in. Humans do not need to run to things that are idolatrous, humans are only assigned to try. This tradition is a ceremony to symbolically get rid of bad luck by bathing the pandhaba child, which people usually call muang setan in the Madurese language. In it there is a reading of stories or ancient stories from the five pandavas about the expulsion of jinn or demons in the form of misfortune in humans to obtain salvation